Faktor-Faktor Yang Mempengaruhi Return Saham Perusahaan Manufaktur Yang Telah Go Publik Di Bursa Efek Indonesia - Alhuda, Addien, Drs. Wiyadi, M.M., Ph.D (2017)
The purpose of this study was to analyze the influence of return on equity, price to earnings, systematic risk, return on assets and capital structure, as measured by debt to asset ratio, debt to equity ratio and the equity to assets ratio of the stock return of manufacturing companies that have gone public in Indonesia Stock Exchange. Based on the results of this study are expected to be considered by prospective investors as a reference in determining the right investments in the capital market, especially when investing in a manufacturing company. The data in this research is secondary data derived from manufacturing companies that have gone public on the Indonesian Stock Exchange. Source data is based on ICMD (International Capital Market Directory). Sample of research is manufacturing companies listed in Indonesia Stock Exchange 2010-2015 period. The analytical tool used to analyze the problems of the multiple linear regression analysis. The results of this study are systematic risk positive and significant effect on stock returns, return on assets positive and significant effect on stock returns, price-to-earnings ratio is not positive and significant effect on stock returns, debt to equity ratio positive and significant effect on stock returns , debt to asset ratio is not positive and significant effect on stock returns, equity to asset ratio is not positive and significant effect on stock returns, return on equity and a significant positive effect on stock returns. The magnitude of the effect of the independent variable on the dependent variable of 5.5%, while the remaining 94.5% is influenced by other variables.